EDUKASI GEMARI (Gemar Makan Ikan) MELALUI METODE ROLE PLAY SERTA PENGOLAHAN IKAN SEBAGAI UPAYA PENINGKATAN GIZI PADA SISWA PESANTREN MODERN YAYASAN BABUL FIKRI KECAMATAN MEUREUBO KABUPATEN ACEH BARAT - Sri Wahyuni Muhsin; Radhi Fadhilah; Rinawati Rinawati; Burhanis Burhanis; Zulfadhli Zulfadhli (Jurnal Marine Kreatif, 2021)
Indonesia is a maritime country and produces a lot of fish, but according to BPS data, the average protein consumption, including Indonesian fish consumption, is 64.64 grams per capita a day, while Aceh is only 58.99 grams per capita a day. This service activity aims to educate students at Islamic boarding schools about the importance of fish consumption, invite students to eat processed fish so that it is hoped that they will be able to increase knowledge and change fish consumption behavior. The participants of this activity were 40 students of the Babul Fikri Islamic Boarding School. The method used is the Role Play method and also uses PPT tools about the importance of fish consumption. Educational results obtained an increase in students' knowledge related to fish consumption as seen from the average value of the level of knowledge, namely (2,625-4.725 = 2.1 points), so we can conclude that the love of eating fish education carried out can increase students' knowledge and will be able to change adolescent behavior behavior that is able to overcome the problem of fish consumption. In addition, it was also seen that there was an increase in fish consumption which was better than before education, from 42.5% to 63.5%.